PENGARUH TABUNGAN MUDHARABAH, PEMBIAYAAN MUDHARABAH-MUSYARAKAH DAN PENDAPATAN OPERASIONAL LAINNYA TERHADAP LABA STUDI PADA BANK JATIM SYARIAH PERIODE 2007-2015 - Purwaningsih, arida (An-Nisbah: Jurnal Ekonomi Syariah, 2016)
The research aims to examine the influence of savings of Mudharabah, financing of Mudharabah-Musharakah and other operating incomes in increasing the profit of Bank Syariah Jatim. The method of analysis in this research used analysis of double linear regression. Populations in the research are the financial report of Bank Syariah Jatim. The results of research showed that the profits will increase as savings of Mudharabah increase. Infinancing of Mudharabah-Musharakah, it happened inversely; when financing declined, the profit would increase. It happened because the financing which attracted by many customers are the ones with the principle of murabahah financing. While, other operational will affect the increase of profits. When other operating incomes increased, the profit would also increase. In the contrast, other operating incomes decreased, the earned profit also would decrease. If all these variables are maximized in its operations, it would assist in increasing the profits at Bank Syariah Jatim.Keywords: Savings of Mudharabah, Financing of Mudharabah-Musharaka,Other Operating Incomes, Profit